The Effect of Dietary Sodium Alginate on the Growth and Survival of Giant Freshwater Prawn (Macrobrachium rosenbergii) - , Rushirajsinh J. Rana, A. S. Kotiya, Mansi D. Jungivala, Kishan Sakariya (Archives of Current Research International, 2025)
The giant freshwater prawn, Macrobrachium rosenbergii, is a valuable aquaculture species known for its rapid growth, adaptability to environmental variations, and high nutritional value. However, challenges such as high mortality rates, algal blooms, dissolved oxygen depletion, and pathogen outbreaks constrain its cultivation. The overuse of antibiotics in aquaculture raises significant environmental and health concerns, including antimicrobial resistance. This study explores the potential of sodium alginate, a natural polysaccharide derived from brown algae, as a prebiotic and immunostimulant for improving growth and feed efficiency in M. rosenbergii. Juvenile prawns (~0.2 g) were cultured for 60 days and fed experimental diets supplemented with sodium alginate at concentrations of 0 g/kg (control, T0), 1.0 g/kg (T1), 2.0 g/kg (T2), and 3.0 g/kg (T3). Growth performance, feed utilization, and survival rates were assessed bi-weekly. Results showed significant improvements (p<0.05) in growth parameters, including mean weight gain (MWG) and specific growth rate (SGR), in prawns fed a 2.0 g/kg sodium alginate diet (T2). At the end of the experiment, T2 recorded the highest mean weight, MWG, SGR, and lowest feed conversion ratio (FCR, 2.395 ± 0.068), demonstrating superior feed utilization efficiency. In contrast, prawns fed a 3.0 g/kg sodium alginate diet (T3) showed reduced growth performance and feed efficiency. This study highlights the efficacy of sodium alginate as a dietary supplement to enhance growth, feed efficiency, and sustainability in freshwater prawn aquaculture, with the optimal dosage identified as 2.0 g/kg. These findings support sodium alginate's potential as an eco-friendly alternative to antibiotics in aquaculture systems.